Two-wavelength WDM multiplexers based on combined fiber structures - D. A. Ivanov; V. I. Nefedov (Российский технологический журнал)
One of the main directions in the development of optical communication systems is associated with the use of optical fiber (ОF) for data reception and transmission. Therefore, manufacturers began to pay special attention to the creation of new brands of OF, improving their optical and operational characteristics. This makes it possible to improve existing optical fiber components that use OF as an active medium. The most widely used are two-wavelength 1 × 2 WDM multiplexers/demultiplexers designed to separate and combine optical carriers with wavelengths of 1310 and 1550 nm, corresponding to the second and third transparency windows of quartz OF. It should be noted that multiplexers and demultiplexers are the same optical devices, which are spectrally selective splitters. Such devices are distinguished by a sufficiently high level of optical characteristics at a relatively low cost of products. However, an analysis of the multiplexers produced in recent years shows that the characteristics of these devices do not sufficiently correspond to the set of modern requirements imposed by most system developers, in particular on permissible values of external influencing factors, insertion loss and the value of optical isolation of channels. Therefore, the development and research of WDM multiplexers with improved optical characteristics is relevant. One of the possible ways of optimizing such devices using new types of OF with resistance to bending losses, of which WDM multiplexers could be made. In this paper, we consider the possibilities of realizing fused single-mode multiplexers/demultiplexers based on combined fiber structures. The technology and equipment for the manufacture of these devices are presented. The optical characteristics of experimental samples of WDM multiplexers are investigated. The results of testing for the effect of temperature are given.